Preliminary, Real-world, Multicenter Experience With Omadacycline for Mycobacterium abscessus Infections. (7th January 2021) - Morrisette, Taylor; Alosaimy, Sara; Philley, Julie V; Wadle, Carly; Howard, Catessa; Webb, Andrew J; Veve, Michael P; Barger, Melissa L; Bouchard, Jeannette; Gore, Tristan W; Lagnf, Abdalhamid M; Ansari, Iman; et al.
Abstract: Twelve patients were treated with omadacycline (OMC) as part of a multidrug regimen for Mycobacterium abscessus . The majority of infections were of pulmonary origin (7/12; 58.3%). The median (interquartile range) duration of OMC was 6.2 (4.2–11.0) months. Clinical success occurred in 9/12 (75.0%) patients. Three patients experienced a possible adverse effect while on therapy.